Tell Me a Story - Alexandre, I.; Brna, P.; Paiva, A. (Virtual Reality, 2005)
For the past few years, the storytelling research domain has raised the interest of several researchers from different areas (such as interactive drama, computer games, intelligent learning environment etc.), mainly because stories are an important vehicle to structure the human knowledge and past experience, and even to help people to behave in a social context. In this paper, we present a storytelling approach, which is based on the premise that story and narrative may emerge from characters' interactions during the creation activity, but such characters may either act autonomously or be controlled by children. Since we position our research in an educational context, we argue that in such creation activities children's thoughts and needs must be respected and contribute directly to the achievement of the story. Therefore, children should be provided with some support and guidance directives to help them to better understand and reflect on the role-taking situations they experience during such activity. To prove the validity of our approach we developed a generic architecture - Support And Guidance Architecture (SAGA). SAGA aims not only to provide support and guidance to children during the story telling activities, by combining the roles of a dynamic script writer and a drama manager, but also to provide such services to already existing story creation applications. To illustrate this, we have integrated SAGA with Teatrix, a collaborative virtual environment for story creation, and an evaluation study was conducted in order to find the impact of SAGA in children's storytelling activities.